Challenges of Workplace Mobbing Prevention in General Education Schools - Vveinhardt, Jolita; Jakucionyte, Ieva (Journal of the University of Zulia, 2023)
Mobbing in general education schools goes beyond the organization, and not only the internal environment of schools but also a wider social context must be evaluated in creating prevention programs. Therefore, this study aims to review and highlight the specific challenges of mobbing prevention in general education institutions. The research was conducted using a semi-systematic review approach. First, a list of relevant terms, which were used to select thematically related articles in scientific databases, was formed. This was followed by reading abstracts and selecting articles for further analysis, which enabled to distinguish relevant categories of prevention challenges. The study has shown that the main challenges arise due to the used management models, inadequate responses of the school administration, the lack of information about mobbing and procedures for solving this problem as well as personal characteristics of the victim and the specific social context. A systematic approach is needed to create prevention programs and conduct research in general education institutions, which would allow not only to evaluate individual and organizational aspects but also to predict the threats arising in the school’s social environment and the ways to minimize them.